Karakteristik Fisik Kimia dan Sensoris Crackers Dengan Tepung Kacang Merah dan Daun Katuk - Dita Andansari (Fakultas Teknologi Pertanian, 2025)
Crackers are a type of flat biscuit typically made from low-protein wheat flour, resulting in a low protein content. This study aims to enhance the nutritional value of crackers by adding red bean flour, which is rich in protein, and katuk leaf flour, which is high in fiber, vitamins, and minerals. The research design used a Completely Randomized Design (CRD) with a single factor, namely the variation in the proportions of wheat flour, red bean flour, and katuk leaf flour across five formulations (A0: 100%-0%-0%, A1: 80%-15%-5%, A2: 60%-35%- 5%, A3: 50%-45%-5%, A4: 20%-75%-5%) and four repetitions for each treatment. The study consisted of three stages: preparation of red bean flour and katuk leaf flour, production of crackers, and analysis of physicochemical and organoleptic characteristics. Physicochemical data analysis was performed using ANOVA at a 95% confidence level, followed by a DMRT test if significant differences were found. The results showed that the physical characteristics of the crackers, in terms of color, had lightness values ranging from 43.65 to 74.22 and hue values from 64.98 to 75.95, with texture ranging from 630.99 gf to 1234.58 gf. The chemical characteristics of the crackers included moisture content (7.78%– 8.62%), ash content (2.2%–3.75%), protein content (14.11%–17.49%), fat content (14.5%–17.82%), and carbohydrate content (53.13%–61.46%). Based on the effectiveness test, the best formulas were A0 (100% wheat flour) and A1 (80% wheat flour, 15% red bean flour, and 5% katuk leaf flour). Formula A1 was selected as the best sample among the crackers substituted with red bean and katuk leaf flour.
Reaploud Repository February_Hasyim
Keywords: crackers; wheat flour; red bean; katuk leaf